AKURASI PERHITUNGAN FULL MOON DENGAN ALGORITMA JEAN MEEUS TERHADAP EPHEMERIS DALAM SISTEM PENANGGALAN KAMARIAH : FULL MOON CALCULATION ACCURACY USING JEAN MEEUS ALGORITHM FOR EPHEMERIS IN THE MOON DATE SYSTEM - Halpi Anti; Muh. Rasywan Syarif; Faisal Akib (HISABUNA: Jurnal Ilmu Falak, 2023)
Abstract In the lunar calendar there are three white days, namely on days where the moon looks bright at night on the 13th, 14th and 15th (full moon), however, to distinguish the 14th and 15th by means of a rukyat in a month is very difficult because in the month full moon reflected moonlight is just as bright so contemporary reckoning is needed. The type of research used is library research with an astronomical and syar'i research approach. equipped with primary data and secondary data. Processing and analysis of data through the process of editing data, transforming data and presenting data. The research results obtained by calculating the full moon with the Jean Meeus algorithm for the month of Ramadan 1444 H, first converting the UT time to JD which is then converted to JDE. Find T to find M, M', F, and Ω. The difference in the calculation results from the Meeus and ephemeris algorithms is very large, around 19h 11m 19d. Meeus uses the long formula while ephemeris uses the RI Ministry of Religion's moon-solar data. Keywords: Algorithm, Ephemeris, Lunar Calendar